An Analysis of Practical Lexicography: A Reader (Ed. Fontenelle 2008) - de Schryver, Gilles-Maurice (Lexikos, 2009)
Abstract: Intended as a companion volume to The Oxford Guide to Practical Lexicography (Atkins and Run-dell 2008), Fontenelle's book aims to bring together the most relevant papers in practical lexicography. This review article presents a critical analysis of the success thereof, both in quantitative and qualitative terms.Keywords: PRACTICAL LEXICOGRAPHY, DICTIONARY, MONOLINGUAL, BILINGUAL, QUANTITATIVE EVALUATION, QUALITATIVE EVALUATION, CITATION PATTERNS, CORPUS TOOLS, MEANING, DEFINITIONS, EXAMPLES, EQUIVALENCE, DICTIONARY USE, ENGLISH, FRENCHSamenvatting: Een analyse van Practical Lexicography: A Reader (Fonte-nelle 2008). Bedoeld als achtergrondlectuur bij The Oxford Guide to Practical Lexicography (Atkins en Rundell 2008), is het doel van Fontenelle's boek om de meest relevante papers m.b.t. praktische lexicografie samen te brengen. Dit recensieartikel is een kritische analyse van het succes daarvan, zowel in kwantitatieve als kwalitatieve termen.Sleutelwoorden: PRAKTISCHE LEXICOGRAFIE, WOORDENBOEK, EENTALIG, TWEE-TALIG, KWANTITATIEVE EVALUATIE, KWALITATIEVE EVALUATIE, CITATIEPATRONEN, CORPUS SOFTWARE, BETEKENIS, DEFINITIES, VOORBEELDEN, EQUIVALENTIE, WOOR-DENBOEKGEBRUIK, ENGELS, FRANS